Forensic Examination in Infanticide Case - Putrie, Hesa Chikita; Mandasari, Safira (Jurnal Medis Islam Internasional, 2024)
Introduction: Infanticide is a crime in which a mother kills her baby during or shortly after birth. In 2020, infanticide cases in Indonesia reached 16.85%. Infanticide is mainly carried out through mechanical asphyxia in the form of smothering and strangulation. Case: The body of an unidentified female newborn baby was found in the Sandubaya area, Mataram City, on Monday, July 10th 2023. The observation was carried out through external and internal examination of the body. Discussion: There were bruises and peeling skin all over the body. The autopsy showed a haemorrhage all over the lower part of the scalp, severe injury to the neck, and blood seepage on the right chest. Conclusions: The cause of death was due to severe neck injury resulting in asphyxia